Geological Setting and Genesis of Vein-hosted Copper Mineralisation at the Onganja Mining District, Namibia - Hales, Matthew Paul (University of the Witwatersrand, Johannesburg, 2024)
The Onganja Mining District is in the Southern Zone of the Damara Orogen, Namibia, and comprises several mining licence areas that have historically produced copper concentrates with accessory Au-Mo-U-REE. The country rocks in the district consist largely of amphibolites, biotite-plagioclase schists, and pelitic schists, with other minor lithologies distributed throughout the licence areas. These rocks have undergone polyphase deformation, which has produced an antiformal dome on which most of the licence areas are located. Initial deformation is recorded by an S1 axial-planar cleavage and locally preserved F1 folds. The F1 folds were refolded by an F2 event that produced a pervasive S2 axial planar cleavage defined by the growth of micas and quartz veins. Progressive deformation and metasomatism focussed along the S2 axial-planar cleavage initiated D3 shearing, which is recognised in the country rocks by an increased mica content, with the micas being well-aligned so as to define a S2,3 transposed schistosity. The development of the shears is most pronounced in the amphibolite units which produced black mica schists that are dominated by a greasy black biotite of phlogopite composition. A N-S trending, steeply east dipping, quartz-albite vein system developed in the ac-plane of the F2 folds. The veins have varying proportions of albite and quartz – typically veins with dominant albite have smoky to translucent quartz, whereas quartz-only veins are typically milky and may have albite haloes. The quartz-albite veins are interpreted to represent metamorphic devolatilization due to the comparable δ18OQuartz values (10.39-14.23 ‰) with those from quartz veins in the Southern Zone related to metamorphic devolatilization reactions while the albite content in these veins is suggested to be related to an increasing metamorphic grade that resulted in fluids more capable of carrying the necessary components for albite formation. The quartz albite veins were crosscut by the D3 shears, which produced breccias that are infilled by various metamorphic, alteration, and ore minerals. In contrast, the calcite vein system differs in orientation and modal mineralogies to the quartz albite veins system and crosscut the D3 shears. Two calcite vein types are recognised: a calcite hematite vein set and a massive calcite vein set. Although both sets contain calcite and crosscut the D3 shears, the relationship between the two is unclear. The calcite-hematite consist of veins with platy hematite and rhombohedral calcite in a matrix of calcite and goethite and have alteration haloes of white mica and albite in the proximal zones and chlorite more distally. The massive calcite veins are, locally ≤1 m wide and dip steeply to the south and the west. These veins consist of large (>2 cm), rhombohedral calcite crystals, incorporate clasts of wall rock and lack associated alteration. Alteration in the district is dominated by albitisation in haloes around fractures and quartz-albite veins, in pressure shadows of quartz lenses in the D3 shears, or as albite lenses in the black-mica schists. Other alteration phases include growth of scapolite, biotite, chlorite, white mica, and quartz. Scapolite occurs within schistosity parallel bands and is interpreted to be comparable to scapolite in shears and thrusts elsewhere in the Southern Zone, even though the scapolite from the district is slightly more sodic (XMe=34-51). Biotite and chlorite both occur with albitisation in the D3 shears forming euhedral crystals in pockets or as trails in the pressure shadows of quartz lenses. Biotite also defines the S2,3 schistosity in the D3 shear, which chlorite does not. Both the biotite and chlorite from the district are enriched in Mg (XMg= ~55-70 and ~60-73, respectively), which is interpreted as a consequence of fluid-rock buffering by iron in the silicates. The fluid-rock buffering and biotite growth is interpreted to have produced a positive feedback loop by which the D3 shears would have developed. The white micas are associated with chlorite, albite, hematite, and goethite. The rocks that have this assemblage are typically pinkish and are collectively called the bleached schists. The white micas are typically euhedral with no preferred orientation, whereas the chlorite may pseudomorph biotite in the deformation fabrics. Hematite and goethite are common and typically occur in association with chlorite and white micas. Owing to the comparable alteration assemblages of the bleached schists and alteration haloes around the calcite-hematite veins, the fluids responsible for both are interpreted to be the same. This alteration is interpreted to be post-kinematic due to the crosscutting of the D3 shears by the calcite-hematite veins and the overprinting of the biotite in the deformation fabrics by the white micas and chlorite. Furthermore, U-Th-Pb age dating of monazite in the bleached schists yields post-orogenic ages of 430-125 Ma. Mineralisation within the district comprises disseminated and massive sulphides within the country rock schists, breccias associated with the quartz-albite vein system, and sulphide veins. The ore assemblage across all styles of ore deposition includes chalcopyrite, chalcocite, pyrite, magnetite, hematite, and molybdenite. The ores are also enriched in Au, U, and REE. Chalcocite is interpreted to be supergene. Pyrite, magnetite and hematite are typically euhedral in all the ore bodies. Molybdenite is locally present as euhedral rosettes. Magnetite typically overgrows pyrite. The disseminated and massive sulphides are dominantly chalcopyrite, whereas the veins and breccias may have varying proportions of chalcocite after chalcopyrite. The sulphide veins consist of chalcocite after chalcopyrite and due to their limited occurrence, little more is known about them. The breccias, disseminated sulphides, and massive sulphides are all spatially related to the black-mica schists. This spatial relationship is suggested to represent a lithological and structural control on the mineralisation as the black-mica schists are interpreted to be the metasomatic product of the D3 shears in the amphibolites. The lithological control is interpreted to be a redox buffer system, with wall rocks that had sufficient Fe content – viz., the amphibolite and black-mica schists – reducing the fluids to cause copper sulphide precipitation. This reduction by the wall rocks is what is likely to have produced the magnetite associated with the copper sulphides. Likewise, hematite is interpreted to be the product of wall rock buffering, however, the wall rocks were likely to have lacked the Fe content to effectively buffer the fluids to the same degree as the black-mica schists. The D3 shears are interpreted to be the conduits through which the ore-bearing fluids migrated – where the shears crosscut compositionally favourable lithologies the copper sulphides were precipitated as disseminated and massive sulphides. Similarly, the shears crosscut the quartz-albite vein system and produce breccias at the intersections. Many of the breccias are barren, having only alteration and metamorphic mineral infill. Where the black mica schists intersect the veins, however, the breccias are mineralised – the wall rocks to the breccias are interpreted to have had the same redox buffering effect as in the D3 shears, however, the preferential fracturing of the quartz-albite veins allowed for the upward escape of the mineralising fluids. The mineralisation and alteration styles at the Onganja Mining District bear some similarity to Iron Oxide-Copper-Gold (IOCG) deposits. These similarities include the Cu-Au-Mo-U-REE element assemblage, the occurrence of magnetite and hematite with the ores, and the albitisation. There are, however, significant differences between the mineralisation in the district and that of IOCG deposits, particularly pertaining to the ore and mineral chemistry. Most notable of the differences is the lack of iron content in the ores (typically <10 wt.%) which has resulted in magnetite and hematite being subordinate to chalcopyrite and phlogopitic biotite (XMg= ~62-67) rather than the Fe-rich biotite of some IOCG deposits. The ores also have geochemical signatures that are distinct from IOCG deposits when comparing the ratio of lithophile (U and La) and chalcophile (Co, Ni, Bi, Se, and Te) to the Cu and Au grades of the ores. Likewise, the minor and trace elements in magnetite from the district are dissimilar to those of select IOCG deposits. It is concluded, therefore, that the mineralisation in the Onganja Mining District is unlikely to be representative of an IOCG system. Rather, the mineralisation bears some similarities to other Pan-African copper deposits associated with domal structures comparable to that on which the district is located. These deposits are defined by Cu mineralisation in late orogenic shears related to retrograde metamorphism and metasomatism. The mineralisation style of the deposits in the Onganja Mining District is, therefore, regarded as late-orogenic, shear-related Cu mineralisation.
A dissertation submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: Copper Mineralisation; Onganja Mining District; D3 shears; Iron Oxide-Copper-Gold (IOCG); Mineral Chemistry; UCTD; SDG-13: Climate action; SDG-11: Sustainable cities and communities